‘Iwaḑ as a Legitimate Condition of Khulu’ (Study on the Analysis of the Decree of the Minister of Religious Affairs No. 411 of 2000 Viewed from the Theory of Al-Maslahah Al-Mursalah): ‘Iwaḑ Sebagai Syarat Sah Khulu’ (Studi Analisis Keputusan Menteri Agama No. 411 Tahun 2000 Ditinjau Dari Teori Al-Maslahah Al-Mursalah) - M. Yunus, Saifullah; Nurakmal, Nurakmal (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2023)
Khulu' is a divorce accompanied by a number of assets as 'iwadh (ransom) given by the wife to her husband to redeem herself so that she is released from the marriage bond. 'iwadh is the reward or ransom given by the wife to her husband to ask for khulu῾. In Indonesia, the nominal value of 'iwadh money has been regulated in the Decree of the Minister of Religion No. 411 of 2000 concerning Determination of the Amount of 'iwadh Money in the series of sighat taklik divorce for Muslims already amounting to Rp. 10,000 of which the money is intended for the amil zakat agency, not for the husband. If these rules are studied from the perspective of Islamic law, there is a significant difference in terms of the number and also the objectives of the 'iwadh. The research questions in this thesis are how the law of 'iwadh as khulu compensation' according to Maslahah Mursalah and whether the Minister of Religion Decree No. 411 of 2000 in accordance with the theory of Maslahah Mursalah. In this study the authors used qualitative research methods and a juridical approach. The results of this study conclude that first, the scholars agree that 'iwadh (ransom) is a pillar that cannot be abandoned in the khulu', when viewed from the perspective of maslahah mursalah then both the wife and husband have the benefit of the wife who asks divorce her husband by returning the dowry to her husband because she is afraid that she will not be able to carry out her obligations as a wife (nusyuz), then she can be released from her marriage bond and the husband does not feel disadvantaged because he gets a ransom from his wife. Second, Decree of the Minister of Religion No. 411 of 2000 concerning Determination of the Amount of 'iwadh Money in the series of sighat taklik divorce for Muslims including maslahah mursalah because if this rule is not regulated it will experience difficulties for the wife and will cause arbitrariness of the husband towards the wife. In this rule, 'iwadh as a result of violating taklik divorce is given to the amil zakat.